Optimization of the osmotic dehydration process for improving the quality of vacuum-fried Vinh Chau shallots at the pilot stage - Ngo Van Tai; Nguyen Minh Thuy (My University, 2023)
1School of Food Industry, King Mongkut’s Institute of Technology Ladkrabang, Bangkok, Thailand 2Institute of Food and Biotechnology, Can Tho University, Vietnam
Keywords: Osmotic dehydration; Garlic and Onion Studies